Pengaruh Buadaya, Sosial dan Pribadi Terhadap Keputusan Pembelian Baju Muslim Pada Toko Butik Arafah Di Situbondo - Yudhistira Harisandi; Widya Fransiska; Rini Kartika Sari (Fakultas Ekonomi Universitas Panca Marga, 2019)
This study aims to determine the effect of partially cultural, social and personal variables on purchasing decision variables, to find out the effect of cultural, social and personal variables together on purchasing decision variables, and to find out which of the cultural, social and personal variables dominantly influence the purchasing decision variable. The data analysis method used in this study is the validity test, reliability test, classic assumption test, multiple linear regression analysis, t-test, f test, dominant test, and coefficient of determination. Partial statistical test or t-test for Cultural variable (X1) shows the value of t arithmetic 2.692> t table 1.985 and significant value t 0.008 <0.050. then H0 is accepted and Ha is rejected. Partially means that the Culture variable (X1) does not have a significant effect on the purchasing decision variable (Y). The results of the t-test for Social variables (X2) show the value of count 3.552> t table 1.985 and significant value t 0.001 <0.050, then H0 is rejected and Ha is accepted. Partially means that the Social variable (X2) has a significant influence on the purchasing decision variable (Y). The results of the t-test for Personal variables (X3) show the value of count 2.198> t table 1.985 and the significant value t 0.03 <0.050, then H0 is rejected and Ha is accepted. Keywords: Culture, Social, Personal, Purchasing Decisions, Muslim Clothing